2006
DOI: 10.1093/ps/85.12.2186
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Dietary Antimicrobial Drug Administration with Broiler Performance, Decreased Population Levels of Lactobacillus salivarius, and Reduced Bile Salt Deconjugation in the Ileum of Broiler Chickens

Abstract: Straight-run broiler chickens were raised either in floor pens or wire-floored cages (trial 1) or in floor pens only (trials 2, 3, and 4). Birds raised in floor pens had lower BW and feed intakes than those raised in cages. The administration of bacitracin in the feed increased feed intake from d 12 to d 35, decreased the feed conversion ratio during the same period in trial 2, and improved the weight gain of broilers from d 0 to 10 in trial 3. The concentrations of conjugated bile salts (taurocholic and tauro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
69
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 31 publications
10
69
2
2
Order By: Relevance
“…Inactivation of bshB in L. acidophilus NCFM revealed that the strain lost hydrolytic activity for tauroconjugated bile salts (40). Given that lactobacilli are the main contributors to Bsh activity in the murine and chicken intestinal tracts (26,56) and could be physiologically important when produced by lactobacilli in the human gut, biochemical characterization of the corresponding Bsh enzymes is desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of bshB in L. acidophilus NCFM revealed that the strain lost hydrolytic activity for tauroconjugated bile salts (40). Given that lactobacilli are the main contributors to Bsh activity in the murine and chicken intestinal tracts (26,56) and could be physiologically important when produced by lactobacilli in the human gut, biochemical characterization of the corresponding Bsh enzymes is desirable.…”
mentioning
confidence: 99%
“…This strain harbors a 242-kb megaplasmid, pMP118, that interdigitates with chromosomally encoded functions to confer metabolic flexibility (35,44). L. salivarius is common in the GI tracts of many animals, including humans (1) and chickens (26), but its survival mechanisms in vivo are poorly understood. In this study, therefore, we examined the contributions of allelic variants of bsh to the bile resistance of L. salivarius, as well as other bile resistance mechanisms.…”
mentioning
confidence: 99%
“…E. coli counts were performed on McConkey agar and incubated for 24h at 37°C. After incubation, colonies formed on the respective media were counted and expressed as Log (CFU) per g of intestinal content (Guban et al, 2006). All microbiological analyses were performed in triplicate, and average values were used for statistical analyses.…”
Section: Effects Of Acidified Yeast and Whey Powder On Performance Omentioning
confidence: 99%
“…Each sample was serially diluted. Using these diluted sub samples, Lactobacillus was enumerated on De Man-RogosaSharpe (MRS) agar after incubation at 37°C in an anaerobic chamber for 48 h (Guban, Korver, Allison, & Tannock, 2006). Coliforms was counted on CHROM agar ECC (EF322-Paris France) after incubation at 37°C in an aerobic chamber for 48 h (Sallam, 2007).…”
Section: Ileal Microfloramentioning
confidence: 99%